Analysis of Marketing Strategies in Enchancing Competitive Advantage in the E-Commerce Industry in the Bangking Sector - Yuliana Dewi; Alfian Mukti Fajar; Nirwana Sampara; Darmawan; Irwan Idrus (www.amertainstitute.com, 2024)
This study aims to analyze the marketing strategies implemented by the e-commerce industry in the banking sector in Parepare City to increase competitive advantage. This research uses a qualitative approach to understand in depth the marketing strategies implemented by the banking sector in the e-commerce industry in Parepare City. This approach was chosen because it allows an in-depth exploration of industry players' experiences, views, and policies. Data was collected through in-depth interviews, observations, and documentation studies, then analyzed thematically to identify patterns, strategies, and critical success factors in creating competitive advantage. This approach is expected to provide a comprehensive picture of the phenomenon under study. The sample in this research consisted of 3 (three) sources who were involved in banking. The results of this research indicate that the marketing strategy implemented by the banking sector in the e-commerce industry in Parepare City plays a significant role in creating a competitive advantage. Implementing digital strategies through mobile banking applications has effectively increased accessibility and interaction with customers.